Amphibole compositions as indicators of deep crustal and mantle processes in subduction zones: case study – Tso Morari metamafics, Ladakh, Himalaya - Singh, Preeti; Pant, NC; Kundu, A; Ahmad, T; Verma, PK (Himalayan Journal of Sciences, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> DOI = 10.3126/hjs.v5i7.1325 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.144